2017
DOI: 10.1128/msphere.00060-17
|View full text |Cite
|
Sign up to set email alerts
|

The Type a and Type b Polysaccharide Capsules Predominate in an International Collection of Invasive Kingella kingae Isolates

Abstract: Kingella kingae has emerged as a significant cause of septic arthritis, osteomyelitis, and bacteremia in young children. A recent study examining a diverse collection of K. kingae isolates from Israel revealed four different polysaccharide capsule types in this species, designated types a to d. To determine the global distribution of K. kingae capsule types, we assembled and capsule typed an international collection of K. kingae isolates. The findings reported here show that the type a and type b capsules repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…The four distinct capsule types of K. kingae promote serum survival in isogenic strains. To date, a total of four distinct capsule types have been identified in diverse collections of K. kingae clinical isolates, including type a ( (19)(20)(21)(22). The prototype strain KK01 used in this study expresses the type a capsule.…”
Section: Opsonin Deposition Is Increased In the Absence Of Surface Pomentioning
confidence: 99%
See 1 more Smart Citation
“…The four distinct capsule types of K. kingae promote serum survival in isogenic strains. To date, a total of four distinct capsule types have been identified in diverse collections of K. kingae clinical isolates, including type a ( (19)(20)(21)(22). The prototype strain KK01 used in this study expresses the type a capsule.…”
Section: Opsonin Deposition Is Increased In the Absence Of Surface Pomentioning
confidence: 99%
“…In K. kingae, four distinct polysaccharide capsules, designated types a, b, c, and d, have been identified (19). Capsule types a and b account for greater than 95% of invasive disease isolates (19,20). Previous work has demonstrated that the capsule is required for full K. kingae virulence in a juvenile rat model of invasive disease (21,22).…”
mentioning
confidence: 99%
“…To our knowledge, no epidemiological data on the healthy carriage is available in France. We aimed to determine the rate of and the factors associated with healthy carriage of K. kingae in young children in France, as well as the capsular serotype of these strains, known to be associated either with invasive or carriage strains [3].…”
mentioning
confidence: 99%
“…Research conducted using a large assortment of international isolates recovered from asymptomatic respiratory carriers and patients with a variety of clinical infections has revealed that K. kingae elaborates a polysaccharide capsule and an exopolysaccharide that confer invasiveness in juvenile animal models (14)(15)(16). Two capsule types (namely, a and b) appear to have enhanced pathogenic properties and are detected in 95% of all isolates from patients with invasive diseases, irrespective of their geographical origin (17,18). Interestingly, capsules c and d are significantly more abundant in isolates from healthy pharyngeal carriers (17).…”
Section: Typing K Kingae Isolates: Invasive Strains and Mucosal Colomentioning
confidence: 99%